Hollow nano flower-shaped Al2O3 loaded Pt-based catalyst as well as preparation method and application thereof

Through the hollow nanoflower-like Al2O3-supported Pt-based catalyst, the problems of low catalyst activity and insufficient hydrogen purity were solved in the microwave-assisted reaction, and efficient dehydrogenation and high-purity hydrogen were achieved, which improved the conversion rate of methylcyclohexane and the stability of the catalyst reduces the preparation cost.

CN119186551APending Publication Date: 2024-12-27ZHEJIANG UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411242533.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-05
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The existing catalysts have low activity, poor selectivity, many by-products in the dehydrogenation reaction of methylcyclohexane, and it is difficult to maintain high purity of hydrogen during efficient dehydrogenation, which limits the application prospects of methylcyclohexane as a hydrogen storage material.

Method used

The hollow nanoflower-like Al2O3-supported Pt-based catalyst was used to prepare hollow nanoflower-like Al2O3 carrier by hydrothermal method, and Pt was loaded under ultrasonic effect using chloroplatinic acid aqueous solution as the impregnation solution to prepare a catalyst with excellent catalytic performance for use in the use of Microwave assisted methylcyclohexane dehydrogenation reaction.

Benefits of technology

It significantly improves the conversion rate of methylcyclohexane, reduces the generation of methane by-products, improves the purity of hydrogen, extends the service life of the catalyst, and reduces the production cost and operational complexity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005029710510000111
    Figure BDA0005029710510000111
  • Figure BDA0005029710510000121
    Figure BDA0005029710510000121
  • Figure HDA0005029710540000011
    Figure HDA0005029710540000011
Patent Text Reader

Abstract

The invention provides a hollow nano flower-shaped Al2O3 loaded Pt-based catalyst as well as a preparation method and application thereof. The preparation method comprises the following steps: in the presence of a precipitator and in the presence of sulfate ions and potassium ions contained in a reaction solution, sequentially carrying out hydrothermal reaction, filtering, cleaning, drying and roasting to obtain the hollow nano flower-shaped Al2O3 carrier, the preparation method comprises the following steps: taking a hollow nano flower-shaped Al2O3 carrier as a raw material, then taking a chloroplatinic acid aqueous solution as impregnation liquid, loading Pt onto the hollow nano flower-shaped Al2O3 carrier by an equivalent-volume impregnation method, drying and roasting to prepare the Pt / Al2O3 catalyst. The preparation process is simple in procedure and mild in condition, and the preparation cost and time are greatly reduced. In the prepared catalyst, potassium ions and sulfate ions can regulate and control the electronic properties of the active components (improve the catalytic performance) and the morphology characteristics of the carrier; the catalyst is used for microwave-assisted methyl cyclohexane dehydrogenation reaction, and has excellent methyl cyclohexane conversion rate and ultrahigh hydrogen purity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of chemical hydrogen storage, and specifically relates to a hollow nano flower-shaped Al 2 O 3 Supported Pt-based catalyst and preparation method and application thereof. Background Art

[0002] Methylcyclohexane (MCH), as an organic compound with a high-density hydrogen content, can efficiently release hydrogen through its decomposition reaction, so it has been widely studied as a hydrogen storage material. MCH can be dehydrogenated to produce toluene and hydrogen under the action of a catalyst. This process shows great application potential in hydrogen storage and transportation. However, in practical applications, traditional catalysts often have problems such as low activity, poor selectivity, and many by-products, which seriously restrict the promotion and application of methylcyclohexane dehydrogenation technology. In addition, the improvement of hydrogen purity also faces many challenges, and further improvement is needed to meet the application requirements of high-precision equipment such as fuel cells, where the hydrogen purity requires to reach more than 99.99%.

[0003] Platinum (Pt)-based catalysts have shown excellent catalytic performance in many high-temperature heating and dehydrogenation reactions due to their high chemical stability and catalytic activity, improving the efficiency of MCH dehydrogenation reaction and the purity of hydrogen. However, despite the outstanding catalytic performance of Pt-based catalysts, their high cost and limited resources make their large-scale application challenging. In addition, the catalyst may deactivate during a long reaction process, which also affects the purity and production efficiency of hydrogen.

[0004] Alumina (Al 2 O 3 ) As a catalyst carrier, it not only has good mechanical strength and thermal stability, but also can provide a large specific surface area, thereby providing more active sites for catalytic reactions. In particular, hollow alumina has attracted widespread attention due to its unique and superior performance. Hollow alumina can effectively disperse active metal particles and prevent particle agglomeration, thereby improving the stability and service life of the catalyst.

[0005] In the existing literature, the patent document with publication number CN118183813A discloses a method for preparing alumina microspheres with a hollow multilayer structure by using sulfonic acid or carboxyl anionic surfactants as templates and controlling the hydrolysis rate of aluminum ions, but the required template content is high and the preparation process is complicated. The patent with patent number CN110841619B discloses a method for preparing porous alumina using a carbon template method, wherein the carbon template CTFs need to be homemade, and the preparation process requires mixing a cyano-containing organic precursor with anhydrous zinc chloride and pre-treating under the protection of an inert atmosphere to remove substances adsorbed in the pores, and the process is cumbersome and complicated. The patent document with publication number CN1884083A discloses a method for preparing a nano-alumina hollow sphere structure, which requires the addition of an organic template or inducer, and the hydrolysis reaction temperature is high, which increases the complexity and cost of the operation.

[0006] Although these methods have improved the performance of the catalyst to a certain extent, they are generally complicated to operate and costly, which limits their application in industrial scale. In addition, the current catalyst system is difficult to maintain high purity of hydrogen while achieving efficient dehydrogenation, which further limits the application prospects of methylcyclohexane as a hydrogen storage material.

[0007] In order to solve these problems, future research directions should focus on the following aspects: improving the preparation process of hollow alumina and reducing production costs; enhancing the stability and anti-deactivation performance of the catalyst and extending its service life to improve the selectivity and hydrogen purity of the MCH dehydrogenation reaction. At the same time, further optimize the design and preparation method of the catalyst, and strive to achieve high-purity output of hydrogen while ensuring high activity and high selectivity. This will pave the way for the practical application of methylcyclohexane as a hydrogen storage material and further promote the development of hydrogen energy technology. Summary of the invention

[0008] In order to solve the problems existing in the prior art, the present invention provides a hollow nano flower-shaped Al 2 O 3 A supported Pt-based catalyst and its preparation method and application. The preparation method of the invention is simple to operate, fast to prepare, and has mild reaction conditions. The prepared catalyst is applied to microwave-assisted methylcyclohexane dehydrogenation reaction, which can significantly improve the conversion rate of methylcyclohexane, significantly reduce the generation of methane byproducts, and effectively improve the purity of product hydrogen.

[0009] A hollow nanoflower-like Al 2 O 3 The preparation method of the supported Pt-based catalyst comprises the following steps:

[0010] (1) adding a precipitant to an aqueous solution containing aluminum ions and sulfate ions, stirring the solution, and then performing a hydrothermal reaction. After the reaction solution is cooled, it is filtered, washed, dried, and calcined in sequence to obtain hollow nanoflower-like Al 2 O 3 Carrier;

[0011] (2) Using the equal volume impregnation method, chloroplatinic acid aqueous solution was used as the impregnation solution, and Pt was loaded onto the hollow nanoflower-like Al 2 O 3 The product is dried and calcined to obtain the hollow nanoflower-like Al 2 O 3 Supported Pt-based catalyst.

[0012] In the above step (1):

[0013] Preferably, aluminum ions (Al 3+ ) is provided by an aluminum salt, wherein the aluminum salt is selected from one or more of aluminum nitrate, aluminum sulfate, potassium aluminum sulfate, and aluminum chloride. More preferably, it is one or more of aluminum nitrate, aluminum sulfate, and potassium aluminum sulfate.

[0014] Preferably, the concentration of aluminum ions in the aqueous solution is 0.1 to 0.5 mol / L, more preferably 0.1 to 0.3 mol / L, and even more preferably 0.2 mol / L.

[0015] Preferably, sulfate ions (SO 4 2- ) is provided by the above-mentioned aluminum salt and / or additives, wherein the additive is selected from one or more of potassium nitrate, ammonium sulfate, potassium sulfate, and potassium chloride. Potassium nitrate, ammonium sulfate or potassium sulfate is further preferred.

[0016] Preferably, the concentration of sulfate ions in the aqueous solution is 0.1 to 0.8 mol / L, more preferably 0.2 to 0.6 mol / L, and even more preferably 0.4 mol / L.

[0017] Preferably, the precipitant is one or more of ammonium carbonate, sodium hydroxide and urea, and more preferably urea.

[0018] Preferably, the amount of the precipitant added to the aqueous solution is 0.2 to 1 mol / L, more preferably 0.3 to 0.7 mol / L, and even more preferably 0.5 mol / L.

[0019] Preferably, the aqueous solution also contains potassium ions, wherein the concentration of potassium ions is 0.1 to 0.5 mol / L, more preferably 0.1 to 0.3 mol / L, and even more preferably 0.2 mol / L.

[0020] As further preferred, potassium ions are provided by the above-mentioned aluminum salt and / or additive.

[0021] Preferably, the hydrothermal reaction temperature is 150-200°C, and the reaction time is 2-4 hours. More preferably, the hydrothermal reaction temperature is 180°C, and the reaction time is 3 hours.

[0022] The reaction liquid can be filtered by a circulating water vacuum pump.

[0023] Preferably, the washing process after filtering the reaction solution includes first washing with deionized water for several times, and then washing with anhydrous ethanol for several times.

[0024] Preferably, the drying temperature is 70 to 90° C., and the drying time is 2 to 4 hours. More preferably, the drying temperature is 80° C., and the drying time is 3 hours.

[0025] Preferably, the calcination temperature is 400-800°C and the calcination time is 1-12 hours. More preferably, the calcination temperature is 500-600°C and the calcination time is 3-6 hours. More preferably, the calcination temperature is 600°C and the calcination time is 3 hours.

[0026] The calcination process can be carried out in a muffle furnace, wherein the heating rate is preferably 3-8°C / min. After the temperature is raised to the calcination temperature, the calcination is carried out at a temperature-keeping rate, and more preferably 5°C / min.

[0027] In the above step (2):

[0028] Preferably, when the volume is equal, the ultrasonic time is 5 min to 1 h, more preferably 5 to 20 min, and even more preferably 10 min.

[0029] Preferably, the drying temperature is 70 to 90° C., and the drying time is 2 to 4 hours. More preferably, the drying temperature is 80° C., and the drying time is 3 hours.

[0030] Preferably, the calcination temperature is 300-600°C and the calcination time is 1-24 hours. More preferably, the calcination temperature is 350-550°C and the calcination time is 3-15 hours. More preferably, the calcination temperature is 350-450°C and the calcination time is 9-15 hours.

[0031] Preferably, the calcination atmosphere is one of hydrogen, air and nitrogen. More preferably, hydrogen is used. More preferably, the amount of hydrogen introduced is 5 to 20 mL / min. More preferably, it is 10 mL / min.

[0032] The calcination reaction can be carried out in a tubular furnace reactor or in other suitable equipment, which is not limited in the present invention. As a further preference, the calcination reaction is carried out in a tubular furnace reactor.

[0033] Preferably, the hollow nanoflower-shaped Al 2 O 3 In the supported Pt-based catalyst, the supported amount of Pt is 0.5 to 5 wt %, more preferably 0.5 to 2.4 wt %, and even more preferably 0.6 wt %.

[0034] As a specific preferred embodiment, a hollow nanoflower-shaped Al 2 O 3 The preparation method of the supported Pt-based catalyst comprises the following steps:

[0035] Step 1: Preparation of hollow nanoflower-like Al by hydrothermal method 2 O 3 Carrier

[0036] The precipitant is placed in a solution containing aluminum ions (Al 3+ ) and sulfate ions (SO 4 2- ) in an aqueous solution to obtain an AlOOH precursor solution, which is then placed in a reactor for hydrothermal reaction; the suspension (reaction solution) after high temperature treatment by the hydrothermal reaction is filtered, washed, dried and calcined to obtain hollow nanoflower-like Al 2 O 3 Carrier;

[0037] Step 2: Preparation of Pt / Al by isovolumetric impregnation method 2 O 3 catalyst

[0038] Using chloroplatinic acid aqueous solution as the impregnation solution, the Pt-loaded hollow nanoflower-like Al 2 O 3 On the support, Pt / Al 2 O 3 Precursor: Pt / Al 2 O 3 The precursor is dried and calcined to obtain Pt / Al 2 O 3 Catalyst (Hollow Nanoflower-like Al 2 O 3 supported Pt-based catalyst).

[0039] A hollow nanoflower-like Al 2 O 3 The Pt-based catalyst is loaded by any of the hollow nanoflower-shaped Al 2 O3 The prepared catalyst is prepared by the preparation method of the supported Pt-based catalyst.

[0040] A hollow nanoflower-shaped Al 2 O 3 Application of supported Pt-based catalysts in microwave-assisted dehydrogenation of methylcyclohexane.

[0041] Specifically, under microwave-assisted heating and induction, hydrogen-assisted conditions, methylcyclohexane was pumped into a gasifier through a liquid pump for gasification, and then a hollow nanoflower-shaped Al 2 O 3 Dehydrogenation reaction is carried out in the bed of a microwave fixed bed reactor loaded with a mixture of a Pt-based catalyst and a microwave absorbing medium, silicon carbide. The reaction product is analyzed by a gas chromatograph after condensation and gas-liquid separation.

[0042] Preferably, in the microwave-assisted dehydrogenation reaction of methylcyclohexane, the hollow nanoflower-shaped Al 2 O 3 The mass ratio of the supported Pt-based catalyst to the microwave absorbing medium silicon carbide is 1:(2-4), and more preferably 1:3.

[0043] As a preferred embodiment, in the microwave fixed bed reactor, the hollow nanoflower-shaped Al 2 O 3 The loading amount of the supported Pt-based catalyst was 200 mg.

[0044] Preferably, the power of the microwave is 300W to 600W.

[0045] Preferably, the vaporization temperature is 100 to 200°C, preferably 150°C.

[0046] Preferably, the dehydrogenation reaction temperature is 300-400°C, and the reaction pressure is 0.05-0.2 MPa. More preferably, the dehydrogenation reaction temperature is 350°C, and the reaction pressure is 0.1 MPa.

[0047] Preferably, the flow rate of the methylcyclohexane liquid pump is 0.05 to 0.2 mL / min, more preferably 0.05 to 0.1 mL / min.

[0048] Preferably, the accompanying flow rate of hydrogen is 1 to 10 mL / min, more preferably 3 to 7 mL / min.

[0049] Preferably, the condensation temperature is 2 to 6°C, more preferably 4°C.

[0050] Compared with the prior art, the present invention has the following beneficial effects:

[0051] The hollow nano flower-shaped Al 2 O3 The preparation method of the supported Pt-based catalyst comprises the following steps: using aluminum salt as a reaction raw material, and in the presence of a precipitant, sulfate ions and potassium ions in the reaction solution, sequentially undergoing hydrothermal reaction, filtering, washing, drying and calcining to obtain hollow nanoflower-shaped Al 2 O 3 The carrier is then impregnated with chloroplatinic acid aqueous solution, and Pt is loaded onto the hollow nanoflower-shaped Al 2 O 3 Pt / Al was prepared by drying and calcining on the support. 2 O 3 Catalyst. The preparation process is simple and mild, which greatly reduces the preparation cost and time. In the prepared catalyst, potassium ions and sulfate ions can regulate the electronic properties of the active components (improve catalytic performance) and the morphological characteristics of the carrier; among them, sulfate ions can promote the formation of hollow nanoflower structures of the carrier and increase Al 2 O 3 The surface is uneven, thus promoting the location of Pt clusters. The presence of potassium ions will preferentially provide electrons to the Pt active sites, effectively reducing the occurrence of hydrogen production side reactions and promoting the generation of high-concentration hydrogen. The prepared catalyst is used for microwave-assisted methylcyclohexane dehydrogenation reaction, with excellent methylcyclohexane conversion rate and ultra-high hydrogen purity. BRIEF DESCRIPTION OF THE DRAWINGS

[0052] Figure 1 X-ray diffraction (XRD) diagrams of the catalysts prepared in Examples 1 to 5 and Comparative Examples 1 to 2;

[0053] Figure 2 is a transmission electron microscope (TEM) image of the catalyst prepared in Comparative Example 1;

[0054] Figure 3 is a transmission electron microscope image of the catalyst prepared in Example 1;

[0055] Figure 4 is a transmission electron microscope image of the catalyst prepared in Example 4;

[0056] Figure 5 is a TEM image of the catalyst prepared in Example 5;

[0057] Figure 6 This is a diagram showing the stability of the catalyst prepared in Example 4 for catalytic dehydrogenation of methylcyclohexane. DETAILED DESCRIPTION

[0058] In order to better understand the present invention, the present invention is described in detail below in conjunction with specific embodiments. In order to elaborate on the present invention, the following examples illustrate many process details, which are not intended to cause improper limitations on the present invention.

[0059] [Example 1]

[0060] Aluminum nitrate was dissolved in deionized water to obtain an aluminum salt aqueous solution with a concentration of 0.2 mol / L, and then urea (concentration of 0.5 mol / L) and ammonium sulfate (concentration of 0.4 mol / L) were added under stirring at room temperature, and the mixture was stirred until clear and allowed to stand for 20 minutes to ensure that the reactants were evenly mixed to obtain a mixed solution;

[0061] The mixed solution was transferred to a stainless steel reactor with a polytetrafluoroethylene liner, sealed, and reacted at 180°C for 3 hours to obtain a reaction solution containing AlOOH; after the reaction solution containing AlOOH was naturally cooled to ambient temperature, it was filtered using a circulating water vacuum pump and washed with deionized water 5 times, then washed with anhydrous ethanol twice, and dried at 80°C for 3 hours to obtain dried AlOOH microspheres; the dried AlOOH microspheres were placed in a muffle furnace, heated to 600°C at a rate of 5°C / min, and kept warm for 3 hours to obtain hollow nanoflower-like AlOOH microspheres. 2 O 3 carrier.

[0062] Chloroplatinic acid was prepared into an aqueous solution (containing 39.2 μg Pt per mL of aqueous solution), and the chloroplatinic acid aqueous solution was impregnated into the hollow nanoflower-like Al by an equal volume impregnation method under the action of ultrasound (10 min). 2 O 3 The slurry was then dried at 80 °C for 3 h and transferred to a tubular furnace reactor into which 10 mL / min of hydrogen was introduced and calcined at 400 °C for 15 h to obtain a 0.6 wt% loaded Pt-based catalyst (Pt / Al 2 O 3 catalyst).

[0063] [Example 2]

[0064] Aluminum sulfate was dissolved in deionized water to obtain an aluminum salt aqueous solution with a concentration of 0.1 mol / L, and then urea (concentration of 0.5 mol / L) and ammonium sulfate (concentration of 0.1 mol / L) were added under stirring at room temperature, and the mixture was stirred until clear and allowed to stand for 20 minutes to ensure that the reactants were evenly mixed to obtain a mixed solution;

[0065] The mixed solution was transferred to a stainless steel reactor with a polytetrafluoroethylene liner, sealed, and reacted at 180°C for 3 hours to obtain a reaction solution containing AlOOH; after the reaction solution containing AlOOH was naturally cooled to ambient temperature, it was filtered using a circulating water vacuum pump and washed with deionized water 5 times, then washed with anhydrous ethanol twice, and dried at 80°C for 3 hours to obtain dried AlOOH microspheres; the dried AlOOH microspheres were placed in a muffle furnace, heated to 600°C at a rate of 5°C / min, and kept warm for 3 hours to obtain hollow nanoflower-like AlOOH microspheres. 2 O 3 carrier.

[0066] Chloroplatinic acid was prepared into an aqueous solution (containing 39.2 μg Pt per mL of aqueous solution), and the chloroplatinic acid aqueous solution was impregnated into the hollow nanoflower-like Al by an equal volume impregnation method under the action of ultrasound (10 min). 2 O 3 The slurry was then dried at 80 °C for 3 h and transferred to a tubular furnace reactor into which 10 mL / min of hydrogen was introduced and calcined at 400 °C for 9 h to obtain a 0.6 wt% loaded Pt-based catalyst (Pt / Al 2 O 3 catalyst).

[0067] [Example 3]

[0068] Aluminum sulfate was dissolved in deionized water to obtain an aluminum salt aqueous solution with a concentration of 0.1 mol / L, and then urea (concentration of 0.5 mol / L) and potassium sulfate (concentration of 0.1 mol / L) were added under stirring at room temperature, and the mixture was stirred until clear and allowed to stand for 20 minutes to ensure that the reactants were evenly mixed to obtain a mixed solution;

[0069] The mixed solution was transferred to a stainless steel reactor with a polytetrafluoroethylene liner, sealed, and reacted at 180°C for 3 hours to obtain a reaction solution containing AlOOH; after the reaction solution containing AlOOH was naturally cooled to ambient temperature, it was filtered using a circulating water vacuum pump and washed with deionized water 5 times, then washed with anhydrous ethanol twice, and dried at 80°C for 3 hours to obtain dried AlOOH microspheres; the dried AlOOH microspheres were placed in a muffle furnace, heated to 600°C at a rate of 5°C / min, and kept warm for 3 hours to obtain hollow nanoflower-like AlOOH microspheres. 2 O 3 carrier.

[0070] Chloroplatinic acid was prepared into an aqueous solution (containing 39.2 μg Pt per mL of aqueous solution), and the chloroplatinic acid aqueous solution was impregnated into the hollow nanoflower-like Al by an equal volume impregnation method under the action of ultrasound (10 min). 2 O 3The slurry was then dried at 80 °C for 3 h and transferred to a tubular furnace reactor into which 10 mL / min of hydrogen was introduced and calcined at 400 °C for 15 h to obtain a 0.6 wt% loaded Pt-based catalyst (Pt / Al 2 O 3 catalyst).

[0071] [Example 4]

[0072] Potassium aluminum sulfate was dissolved in deionized water to obtain an aluminum salt aqueous solution with a concentration of 0.2 mol / L, and then urea (concentration of 0.5 mol / L) was added under stirring at room temperature, and the mixture was stirred until it was clear and allowed to stand for 20 minutes to ensure that the reactants were evenly mixed to obtain a mixed solution;

[0073] The mixed solution was transferred to a stainless steel reactor with a polytetrafluoroethylene liner, sealed, and reacted at 180°C for 3 hours to obtain a reaction solution containing AlOOH; after the reaction solution containing AlOOH was naturally cooled to ambient temperature, it was filtered using a circulating water vacuum pump and washed with deionized water 5 times, then washed with anhydrous ethanol twice, and dried at 80°C for 3 hours to obtain dried AlOOH microspheres; the dried AlOOH microspheres were placed in a muffle furnace, heated to 600°C at a rate of 5°C / min, and kept warm for 3 hours to obtain hollow nanoflower-like AlOOH microspheres. 2 O 3 carrier.

[0074] Chloroplatinic acid was prepared into an aqueous solution (containing 39.2 μg Pt per mL of aqueous solution), and the chloroplatinic acid aqueous solution was impregnated into the hollow nanoflower-like Al by an equal volume impregnation method under the action of ultrasound (10 min). 2 O 3 The slurry was then dried at 80 °C for 3 h and transferred to a tubular furnace reactor into which 10 mL / min of hydrogen was introduced and calcined at 400 °C for 15 h to obtain a 0.6 wt% loaded Pt-based catalyst (Pt / Al 2 O 3 catalyst).

[0075] [Example 5]

[0076] Potassium aluminum sulfate was dissolved in deionized water to obtain an aluminum salt aqueous solution with a concentration of 0.2 mol / L, and then urea (concentration of 0.5 mol / L) was added under stirring at room temperature, and the mixture was stirred until it was clear and allowed to stand for 20 minutes to ensure that the reactants were evenly mixed to obtain a mixed solution;

[0077] The mixed solution was transferred to a stainless steel reactor with a polytetrafluoroethylene liner, sealed, and reacted at 150°C for 6 hours to obtain a reaction solution containing AlOOH; after the reaction solution containing AlOOH was naturally cooled to ambient temperature, it was filtered using a circulating water vacuum pump and washed with deionized water 5 times, then washed with anhydrous ethanol twice, and dried at 80°C for 3 hours to obtain dried AlOOH microspheres; the dried AlOOH microspheres were placed in a muffle furnace, heated to 500°C at a rate of 5°C / min, and kept warm for 6 hours to obtain 1 / 2 hollow nanoflower-like Al 2 O 3 carrier.

[0078] Chloroplatinic acid was prepared into an aqueous solution (containing 39.2 μg Pt per mL of aqueous solution). Under the action of ultrasound (10 min), the chloroplatinic acid aqueous solution was impregnated into 1 / 2 of the hollow nanoflower-shaped Al by an equal volume impregnation method. 2 O 3 The slurry was then dried at 80 °C for 3 h and transferred to a tubular furnace reactor, where 10 mL / min of hydrogen was introduced and calcined at 550 °C for 3 h to obtain a 0.6 wt% loaded Pt-based catalyst (Pt / Al 2 O 3 catalyst).

[0079] [Comparative Example 1]

[0080] Aluminum nitrate was dissolved in deionized water to obtain an aluminum salt aqueous solution with a concentration of 0.2 mol / L, and then urea (concentration of 0.5 mol / L) was added under stirring at room temperature, and the mixture was stirred until it was clear and allowed to stand for 20 minutes to ensure that the reactants were evenly mixed to obtain a mixed solution;

[0081] The mixed solution was transferred to a stainless steel reactor with a polytetrafluoroethylene liner, sealed, and reacted at 180°C for 3 hours to obtain a reaction solution containing AlOOH; after the reaction solution containing AlOOH was naturally cooled to ambient temperature, it was filtered using a circulating water vacuum pump and washed with deionized water 5 times, then washed with anhydrous ethanol twice, and dried at 80°C for 3 hours to obtain dried AlOOH microspheres; the dried AlOOH microspheres were placed in a muffle furnace, heated to 600°C at a rate of 5°C / min, and kept warm for 3 hours to obtain rod-shaped AlOOH microspheres. 2 O 3 carrier.

[0082] Chloroplatinic acid was prepared into an aqueous solution (containing 39.2 μg Pt per mL of aqueous solution), and the chloroplatinic acid aqueous solution was impregnated into the rod-shaped Al by an equal volume impregnation method under the action of ultrasound (10 min). 2 O 3The slurry was then dried at 80 °C for 3 h and transferred to a tubular furnace reactor, where 10 mL / min of hydrogen was introduced and calcined at 350 °C for 15 h to obtain a 0.6 wt% loaded Pt-based catalyst (Pt / Al 2 O 3 catalyst).

[0083] [Comparative Example 2]

[0084] Aluminum nitrate was dissolved in deionized water to obtain an aluminum salt aqueous solution with a concentration of 0.2 mol / L, and then urea (concentration of 0.5 mol / L) and potassium nitrate (concentration of 0.2 mol / L) were added under stirring at room temperature, and the mixture was stirred until clear and allowed to stand for 20 minutes to ensure that the reactants were evenly mixed to obtain a mixed solution;

[0085] The mixed solution was transferred to a stainless steel reactor with a polytetrafluoroethylene liner, sealed, and reacted at 180°C for 3 hours to obtain a reaction solution containing AlOOH; after the reaction solution containing AlOOH was naturally cooled to ambient temperature, it was filtered using a circulating water vacuum pump and washed with deionized water 5 times, then washed with anhydrous ethanol twice, and dried at 80°C for 3 hours to obtain dried AlOOH microspheres; the dried AlOOH microspheres were placed in a muffle furnace, heated to 600°C at a rate of 5°C / min, and kept warm for 3 hours to obtain rod-shaped AlOOH microspheres. 2 O 3 carrier.

[0086] Chloroplatinic acid was prepared into an aqueous solution (containing 39.2 μg Pt per mL of aqueous solution), and the chloroplatinic acid aqueous solution was impregnated into the rod-shaped Al by an equal volume impregnation method under the action of ultrasound (10 min). 2 O 3 The slurry was then dried at 80 °C for 3 h and transferred to a tubular furnace reactor into which 10 mL / min of hydrogen was introduced and calcined at 400 °C for 9 h to obtain a 0.6 wt% loaded Pt-based catalyst (Pt / Al 2 O 3 catalyst).

[0087] Product Characterization:

[0088] The XRD patterns of the Pt-based catalysts prepared in Comparative Examples 1, 2 and Examples 1 to 5 are as follows: Figure 1 As shown by Figure 1 It can be seen that all the Pt-based catalysts prepared in Comparative Examples 1, 2 and Examples 1 to 5 show γ-Al 2 O 3 characteristic peaks.

[0089] The TEM image of the Pt-based catalyst prepared in Comparative Example 1 is as follows: Figure 2 As shown by Figure 2 It can be seen that the appearance of the catalyst is rod-shaped Al 2 O 3 , with an average length of 90nm.

[0090] The TEM image of the Pt-based catalyst prepared in Example 1 is as follows: Figure 3 As shown by Figure 3 It can be seen that the appearance of the catalyst is hollow nanoflower-like Al 2 O 3 , the average particle size is 5μm.

[0091] contrast Figure 2 and 3 It can be seen that the presence of sulfate ions in the mixed solution undergoing hydrothermal reaction can promote the 2 O 3 The carrier forms a hollow nanoflower-like structure, which is also a key factor in the formation of this structure.

[0092] The TEM image of the Pt-based catalyst prepared in Example 4 is as follows: Figure 4 As shown by Figure 4 It can be seen that the appearance of the catalyst is hollow nanoflower-like Al 2 O 3 , the average particle size is 3.3μm.

[0093] The hollow nanoflower-like Al 2 O 3 TEM images of supported Pt-based catalysts are shown in Figure 2. Figure 5 As shown by Figure 5 It can be seen that the appearance of the catalyst is 1 / 2 hollow nanoflower-like Al 2 O 3 , with an average particle size of 3.2 μm, but no complete hollow nanoflower structure was formed.

[0094] contrast Figure 4 and 5 It can be seen that the hydrothermal reaction temperature and time, as well as the calcination temperature and time in the tubular furnace reactor, will also affect the morphology of the catalyst. Figure 3 and 4 It can be seen that the presence or absence of potassium ions can form a complete hollow nanoflower-like structure of Al 2 O 3 carrier.

[0095] Performance Testing:

[0096] Test method: Methylcyclohexane with a purity greater than 99% is pumped into a gasifier through a liquid pump for gasification, and then passed into a microwave fixed bed reactor containing a uniform mixture of 200 mg catalyst and 600 mg silicon carbide SiC. Dehydrogenation reaction is carried out under microwave assisted heating and induction, accompanied by hydrogen. After condensation and gas-liquid separation, the product is analyzed by gas chromatography. Reaction conditions: gasification temperature is 150°C, microwave power is 300W; reaction temperature is 350°C, reaction pressure is 0.1Mpa; condensation temperature is 4°C; methylcyclohexane liquid space velocity (liquid pump flow) is 0.1mL / min, and hydrogen is carried at 5mL / min.

[0097] The above-mentioned test method was used to test the dehydrogenation reaction of methylcyclohexane catalyzed by the Pt-based catalysts prepared in Comparative Examples 1 and 2 and Examples 1 to 5, and the obtained products were analyzed by gas chromatography, wherein the results of the catalytic dehydrogenation reaction for 1 hour are shown in Table 1; at the same time, the results of the dehydrogenation reaction of methylcyclohexane after 24 hours of reaction are shown in Table 2.

[0098] Table 1 Product analysis results of methylcyclohexane dehydrogenation catalysis for 1 h

[0099]

[0100] It can be seen from Table 1 that compared with Comparative Example 1, the Pt / Al 2 O 3 The catalyst has higher methylcyclohexane selectivity, lower methane production, and higher hydrogen purity; combined Figure 2 and 3 The comparison further illustrates that the presence of sulfate ions can be stored in the carrier to form a hollow nanoflower structure, thereby affecting the catalytic performance of the final catalyst. 2 O 3 The catalyst exhibited excellent initial methylcyclohexane selectivity, extremely low methane production and ultra-high hydrogen purity, that is, the raw materials and experimental conditions used to prepare the catalyst were optimal, so that it had the highest CH bond activation ability, and the cleavage of the CC bond was also suppressed; indicating that in the presence of sulfate ions, the addition of potassium ions can further improve the purity of the reaction product hydrogen and further reduce the production of byproduct methane. 2 O 3 The methylcyclohexane selectivity and hydrogen purity of the catalyst were relatively poor, which may be due to the low hydrothermal reaction temperature and time, as well as the calcination time in the tubular furnace reactor, resulting in poor catalyst performance.

[0101] Table 2 Product analysis results of methylcyclohexane dehydrogenation catalysis for 24h

[0102]

[0103] As can be seen from Table 2, the Pt-based catalysts prepared in the above-mentioned Comparative Examples 1, 2 and Examples 1 to 5 still have excellent toluene selectivity and hydrogen purity in the catalytic dehydrogenation reaction of methylcyclohexane after 24 hours of catalytic reaction, compared with the result of 1 hour of catalytic dehydrogenation reaction; only the conversion rate of methylcyclohexane has decreased. Among them, the Pt-based catalysts prepared in Comparative Example 2, Examples 3 and 4 all show excellent stability; and the presence of sulfate in Examples 1-4 will also make the catalyst resist deactivation and reduce CC cracking, improve hydrogen purity, and reduce the reduction in the conversion rate of methylcyclohexane. Among them, the conversion rate of methylcyclohexane of the Pt-based catalysts prepared in Examples 3 and 4 has basically not changed, and the hydrogen purity can reach 99.999%.

[0104] Long-term evaluation of catalytic performance:

[0105] The Pt / Al prepared in Example 4 was tested according to the above performance test method. 2 O 3 The catalyst was evaluated for catalytic performance over a long period of 158 hours, and the obtained product was tested by gas chromatography. Figure 6 As shown. Figure 6 It can be seen that in the long-term evaluation of 158h, the hollow nanoflower-like Al 2 O 3 Supported Pt-based catalyst (Pt / Al 2 O 3 ) showed excellent performance, the content of methane by-product continued to remain at an extremely low level (<3ppm), the methylcyclohexane conversion rate increased from 79.5% to 80.9%, and the toluene selectivity always remained at 99.9%, showing excellent stability.

[0106] The performance test results of the above embodiments show that the hollow nanoflower-shaped Al 2 O 3 The supported Pt-based catalyst exhibits higher methylcyclohexane conversion and hydrogen purity, as well as better stability in the methylcyclohexane dehydrogenation reaction.

[0107] The above description is only a preferred embodiment of the present invention. Within the scope of the principle of the present invention, those skilled in the art may make several improvements and modifications, which should also be considered as the protection scope of the present invention.

Claims

1. A method for preparing a hollow nanoflower-shaped Al2O3-supported Pt-based catalyst, characterized in that: The following steps are involved: (1) adding a precipitant to an aqueous solution containing aluminum ions and sulfate ions, stirring and dissolving, and then performing a hydrothermal reaction. After the reaction solution is cooled, it is filtered, washed, dried, and calcined in sequence to obtain a hollow nanoflower-like Al2O3 carrier; (2) using an equal volume impregnation method, using chloroplatinic acid aqueous solution as the impregnation solution, and loading Pt onto the hollow nanoflower-like Al2O3 carrier under ultrasonic action, and the product is dried and calcined to obtain the hollow nanoflower-like Al2O3-loaded Pt-based catalyst.

2. The method for preparing the hollow nanoflower-shaped Al2O3-supported Pt-based catalyst according to claim 1, characterized in that: In step (1), the concentration of aluminum ions in the aqueous solution is 0.1 to 0.5 mol / L.

3. The method for preparing the hollow nanoflower-shaped Al2O3-supported Pt-based catalyst according to claim 1, characterized in that: In step (1), the concentration of sulfate ions in the aqueous solution is 0.1 to 0.8 mol / L.

4. The method for preparing the hollow nanoflower-shaped Al2O3-supported Pt-based catalyst according to claim 1, characterized in that: In step (1), the precipitating agent is one or more of ammonium carbonate, sodium hydroxide, and urea; The amount of precipitant added to the aqueous solution is 0.2-1 mol / L.

5. The method for preparing hollow nanoflower-shaped Al2O3-supported Pt-based catalyst according to claim 1, characterized in that: In step (1), the aqueous solution also contains potassium ions, wherein the concentration of potassium ions is 0.1 to 0.5 mol / L.

6. The method for preparing the hollow nanoflower-shaped Al2O3-supported Pt-based catalyst according to claim 1, characterized in that: In step (1), the hydrothermal reaction temperature is 150-200° C., and the reaction time is 2-4 h; The calcination temperature is 400-800°C, and the calcination time is 1-12h.

7. The method for preparing hollow nanoflower-shaped Al2O3-supported Pt-based catalyst according to claim 1, characterized in that: In step (2), the calcination temperature is 300-600° C. and the calcination time is 1-24 hours.

8. The method for preparing hollow nanoflower-shaped Al2O3-supported Pt-based catalyst according to claim 1, characterized in that: In the hollow nanoflower-shaped Al2O3-loaded Pt-based catalyst, the loading amount of Pt is 0.5-5 wt%.

9. A hollow nanoflower-shaped Al2O3-supported Pt-based catalyst, characterized in that: The hollow nanoflower-shaped Al2O3-loaded Pt-based catalyst is prepared by the preparation method of any one of claims 1 to 8.

10. Use of the hollow nanoflower-shaped Al2O3-supported Pt-based catalyst as claimed in claim 9 in microwave-assisted dehydrogenation of methylcyclohexane.

Citation Information

Patent Citations

  • Uniform platinum-loaded alumina catalyst, and preparation method and application method thereof

    CN115485064A

  • Platinum-supported alumina catalyst, method for producing same, and method for dehydrogenation of hydrogenated aromatic compound using same

    CN116171197A

  • Dehydrogenation catalyst, preparation method and application thereof, and methylcyclohexane dehydrogenation method

    CN117920257A

  • Preparation method of sulfur-containing Pt-based catalyst

    CN118162160A